Optimisation of flow cytometric detection of intracellular SLAMF receptor-associated adaptor proteins SAP and EAT-2 - Huniadi Mykhailo; Salanci Simon; Sykora Jan; Kurhajec Slavomir; Sarissky Marek (Sciendo, 2022)
SAP and EAT-2 are intracellular adaptor proteins that link SLAMF receptors to downstream intracellular signalling pathways. Their expression and functions vary among different types of hematopoietic cells. The roles of SAP and EAT-2 in haematological malignancies are poorly understood. Here, we attempted to optimise a method for the detection of intracellular SAP and EAT-2 by flow cytometry. We found that using PerFix EXPOSE kit for cell fixation and permeabilization ensures optimal results in terms of staining intensity and signal-to-noise ratio.